Simplemind y su aporte en el aprendizaje colaborativo en los estudiantes de la Carrera de Pedagogía de las Ciencias Experimentales Informática de la Universidad Técnica de Babahoyo, periodo académico Octubre 2024 - Marzo 2025. - Banchen Mata, Nahomi Gimabel (2025)
The impact of technology in education has facilitated not only the presentation of information, but also promotes more interactive and dynamic learning methods. It is proposed that tools such as SimpleMind can improve knowledge organization, promote reading comprehension and facilitate collaborative work among students. A quasi-experimental approach is described in which a sample of students from the Universidad Técnica de Babahoyo of the Pedagogy of Experimental Sciences and Computer Science career was selected. Through data collection techniques, an evaluation of the effects of the implementation of SimpleMind on student learning was carried out. On the other hand, the results show that 47.5% of the respondents consider that collaborative learning has a significant impact on students' motivation. In addition, 50.3% of the respondents believe that this method is highly effective in achieving learning objectives. The research also concludes that SimpleMind not only improves reading comprehension, but also makes.